Apuntes sobre la cosmovisión Andina - Sánchez Arjona, Rodrigo (1971)
The religiosity of man is part of the framework of his own worldview. ALLPANCHIS PHUTURINQA, in its No. 2, has published, under the title "Some philosophical concepts of the Quechua indigenous worldview" by Dr. José Tamayo Herera, one of the first essays on the subject.